(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
We continue in this work studying a new Algol (Arabic name) star, which we discovered during our survey on a field located at the edge of the Pleiades open cluster. We have observed this field in the period 2007 – 2010 with three different CCD-cameras at the University Observatory Jena in Germany using three telescopes from 0.25 to 0.9 m. Our discovered star has an orbital period of days. The location of this star in the HRD is consistent with the age and distance of the already known Pleiades stars in this field. The derived spectral type of the primary star is G9 and K7 for the secondary one. Assuming that our star is a main-sequence star, the derived mass and radius are and for the primary, and for the secondary. refers to the primary star, where refers to the secondary star. is the solar mass, and is the solar radius.